CTLA4 blockade reduces immature myeloid cells in head and neck squamous cell carcinoma. (2nd June 2016) - Yu, Guang-Tao; Bu, Lin-Lin; Zhao, Yu-Yue; Mao, Liang; Deng, Wei-Wei; Wu, Tian-Fu; Zhang, Wen-Feng; Sun, Zhi-Jun
ABSTRACT: Immature myeloid cells such as myeloid-derived suppressor cells (MDSCs) and M2 macrophages play a vital role in the tumor immune escape and tumor progression. Cytotoxic T lymphocyte-associated antigen 4 (CTLA4), as a negative immune checkpoint, is highly expressed in numerous solid tumors. However, precise functions of CTLA4 in head and neck squamous cell carcinoma (HNSCC) have not yet been elucidated. In this study, we demonstrated that the ratio of CD8 + /CTLA4 can be used as a potential index with a clinical prognostic value for HNSCC. Using immunocompetent transgenic mouse model with spontaneous HNSCC, we directly observed that targeting CTLA4 decreases MDSCs and M2 macrophages and promotes T cell activation in both tumor microenvironment and macro-environment. In all, our study provides direct evidence in vivo and proposes a rationale for CTLA4 inhibition as a future therapeutic strategy in patients with HNSCC.